Static and Modal Analysis of a Box Structured Satellite Deployment Mechanism with Self-Actuated Torsion Joint - Sheng, Dongping; Ma, Renzhe; Su, Chun (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
A brand-new satellite deployment mechanism with boxed structure and self-actuated torsion joints is proposed and an effective method to verify the feasibility of this mechanism is established in this paper. This mechanism has the characteristics of high base frequency, high ratio of deployed and folded space occupation ratio. In order to meet the design requirements, the related analysis and optimization need to be conducted, and several conclusions are obtained. Firstly, the modal analysis of deployment mechanism at folded and fully deployed state is analyzed, and the result showed that the proper wall thickness is the key parameter to satisfy the design requirement and an optimized value could be obtained; Secondly, the heat deformation analysis result showed that the material plays an more important roll on affecting the thermal deformation than structure parameter; Thirdly, Under the torsional moment of the joints, the stress distribution of the deployment mechanism under different folding angle is investigated, it could be clearly found that the maximum stress is always located on the bonded area of the rod and joint, and the maximum stress is increased with the opening angle generally. By combined analysis including thermal, static, and modal, the related characteristics are obtained which could be used for structure optimization and provide an effective solution for the design of box structured satellite unfolding mechanism with self-actuated torsional joints.